Bladder Wall Calcification Following Transurethral Resection of Bladder Tumor and Intravesical Mitomycin C Instillation - Perz, Sarah K.; Tenbrink, Patrick M; Haselhuhn, Gregory H. (Translation: The University of Toledo Journal of Medical Sciences, 2018)
In rarely reported instances, the use of intravesical mitomycin C appears to have caused bladder wall calcification. We report two patients treated for non-invasive urothelial carcinoma of the bladder with transurethral resection and mitomycin c instillation. Both of these patients experienced new onset of severe irritative voiding symptoms shortly thereafter. Although one patient com- pleted a six-cycle course of Bacillus Calmette-Guerin (BCG), the other only received one instillation due to symptom severity. On cystoscopy the resection beds appeared calcified and necrotic. Biopsies revealed dystrophic calcification and necrosis without evidence of tumor. Resection of this area led to complete resolu- tion of symptoms and normal healing of the resection site. Our results are consistent with the current hypothesis that these cal- cifications are not related to recurrence or persistence of tumor. Although there have not been reported cases of these calcifica- tions signifying recurrence of tumor, it is important for clinicians to rule out recurrence as a cause for these symptoms. Resection of the area has the added benefit of alleviation of irritative void- ing symptoms encountered shortly after mitomycin c instillation.